2021
DOI: 10.1016/j.neuroimage.2021.118011
|View full text |Cite
|
Sign up to set email alerts
|

Association between hippocampal structure and serum Brain-Derived Neurotrophic Factor (BDNF) in healthy adults: A registered report

Abstract: The hippocampus is a highly plastic brain structure supporting functions central to human cognition. Morphological changes in the hippocampus have been implicated in development, aging, as well as in a broad range of neurological and psychiatric disorders. A growing body of research suggests that hippocampal plasticity is closely linked to the actions of brain-derived neurotrophic factor (BDNF). However, evidence on the relationship between hippocampal volume (HCV) and peripheral BDNF levels is scarce and limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 112 publications
0
24
0
Order By: Relevance
“…In addition, since BDNF crosses the blood-brain barrier (Pan et al, 1998), BDNF in the brain and periphery may affect hippocampal volume. For example, a recent study examining the relationship between hippocampal volume and serum BDNF concentrations in healthy controls found no relationship between the hippocampal volumes and serum BDNF concentrations (Puhlmann et al, 2021). From these findings into account, we hypothesized that hippocampal volume would be decreased in patients with MD as compared with healthy controls, and that BDNF concentrations would be positively correlated with hippocampal volumes.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, since BDNF crosses the blood-brain barrier (Pan et al, 1998), BDNF in the brain and periphery may affect hippocampal volume. For example, a recent study examining the relationship between hippocampal volume and serum BDNF concentrations in healthy controls found no relationship between the hippocampal volumes and serum BDNF concentrations (Puhlmann et al, 2021). From these findings into account, we hypothesized that hippocampal volume would be decreased in patients with MD as compared with healthy controls, and that BDNF concentrations would be positively correlated with hippocampal volumes.…”
Section: Introductionmentioning
confidence: 94%
“…Further 24 subjects were excluded due to missing data in one or more of the predictor variables (for details see 3.1), resulting in a final sample of 106 participants. Although the data reported here were previously published in the context of other research questions ( Engert et al, 2016 , 2017 , 2018 ; Puhlmann et al, 2019 , 2021a , 2021b ), none of these studies linked measures of acute stress responsivity to measures of long-term stress and health. The current study is an a-posteriori exploratory study not planned during the designing of the ReSource Project .…”
Section: Methodsmentioning
confidence: 95%
“…VEGF is another important protein growth factor, as it can directly regulate the ion channels on the cell membrane of neurons, regulate the development and regeneration of neurons, and exert neuroprotective effects [ 34 ]. Brain–derived neurotrophic factors are mainly active in the hippocampus and cerebral cortex, and they play a neuroprotective effect by binding to receptors and promoting the proliferation, differentiation, and migration of NSCs [ 35 ]. In the work of Miller’s research team, it was found that metformin can stimulate the aPKC–CBP signaling pathway and promote the regeneration and development of neurons in the mouse brain [ 21 ].…”
Section: Discussionmentioning
confidence: 99%